Kodeks; Digkuns, Smee(d)kuns: die ontmoeting tussen beeld en woord - Barkhuizen, Gerhard M (School of Languages and Literatures, 2019)
Creative portfolio and essay submitted in fulfillment of the requirements for the degree Masters in Creative Writing.